2013
DOI: 10.1038/bjc.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer efficacy of cisplatin and trichostatin A or 5-aza-2′-deoxycytidine on ovarian cancer

Abstract: Background:To evaluate the anticancer efficacy of the combination of epigenetic modifiers and cisplatin in human ovarian cancer.Methods:The effect of trichostatin A (TSA) and 5-aza-2′-deoxycytidine alone or in combination with low-dose cisplatin was evaluated on human ovarian cancer cell lines in vitro. We measured drug interaction by MTS assay, migration by transwell assay, expression of epithelial to mesenchymal transition (EMT) markers (Twist, Snail, Slug, E-cadherin, and N-cadherin), pluripotency markers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 37 publications
(38 reference statements)
2
37
0
Order By: Relevance
“…The demethylation agent 5-AZA is an effective anticancer therapy (24,25). In the current study, 5-AZA treatment rescued the expression of GATA5 mRNA by reversing GATA5 hypermethylation in HCC cell lines.…”
Section: A B C D Ementioning
confidence: 72%
“…The demethylation agent 5-AZA is an effective anticancer therapy (24,25). In the current study, 5-AZA treatment rescued the expression of GATA5 mRNA by reversing GATA5 hypermethylation in HCC cell lines.…”
Section: A B C D Ementioning
confidence: 72%
“…Combination treatment of TSA and cisplatin showed better efficacy than single drugs and significantly suppressed cell viability, migration, and spheroid formation and growth in human ovarian cancer cells. 51 The combined treatment of TSA and cisplatin synergistically inhibited cell proliferation, induced apoptosis, and increased the inhibition rate via significant decrease of cFLIP expression and increase of caspase-8 in A549 cells. 55 Similarly, TSA combined with palladium nanoparticles (PdNPs) showed an excellent synergistic effect on apoptosis in human cervical cancer cells.…”
Section: Combination Effect Of Rgo-ag and Tsa On Cell Viability And Cmentioning
confidence: 93%
“…50 Meng et al found that TSA inhibits the cell viability of SKOV3 in a dosedependent manner. 51 In another study, rheumatoid arthritis fibroblasts (RA-FLSs) like synoviocytes were subjected to hypoxia for 24 h in the presence or absence of 2 µM TSA and tested for cell viability, apoptosis, invasion, and gene expression. The results from this study suggested that TSA at a concentration up to 2 µM did not affect the viability of normal FLSs, and similarly, the hypoxic exposure did not affect the viability and apoptosis of RA-FLSs after 48-h incubation.…”
mentioning
confidence: 99%
“…Cisplatin is used in combination with other chemical agents or compounds to treat ovarian cancer in both the resistant and sensitive cell lines. For example Cisplatin is used along with honey venom (Alizadehnohi, Nabiuni et al, 2012), withaferin (Kakar, Jala et al, 2012), trichostatin A or 5-aza-2′-deoxycytidine (Meng, Sun et al, 2013), overcoming chemotherapy resistance of ovarian cancer cells by liposomal Cisplatin (Koch, Krieger et al, 2013)…”
Section: Uses Of Cisplatin For Cancer Treatmentmentioning
confidence: 99%